54. Stereotactic plans quality assurance with Delta 4PT phantom. (December 2017) - Berger, L.; Chassin, V.
Abstract : Introduction: As treatment plans of intra and extracranial stereotactic radiotherapy do not benefit in vivo dosimetry, it is a common practice to perform a pretreatment quality control of the dose calculated by the treatment planning system (TPS). In the midst of the different solutions proposed in terms of detectors, we wanted to evaluate the performances of the Delta 4PT (Scandidos) phantom for the measurement of dynamic conformal arctherapy fields. We were then able to define evaluation criteria which proved to be suitable for the whole range of field dimensions in stereotactic radiotherapy (fields of 10 × 10 mm and more). Methods: At the Jean PERRIN center, stereotactic radiotherapy treatment plans are mainly calculated with the iPlan TPS from Brainlab (v4.5). A dedicated module, "Phantom Mapping 4.5.4", allows to calculate the plan on the Delta 4PT phantom CT image. The treatments were then delivered by a Novalis TrueBeam STX linear accelerator (Varian) for 6 MV photon beams in FFF (Flattening Filter Free) mode. The Delta 4PT used for the measurement is a cylindrical PMMA phantom containing 2 planes of orthogonal p-Si detectors. These very small volume detectors are spaced 5 mm apart on a surface of 6 × 6 cm in the center then every 10 mm on the perimeter. The Delta 4PT has been previously calibrated for energy 6 FFF to take into account the energy response. We also took advantage of the "High Resolution" option of the Delta 4PT phantom to double the longitudinal resolution (2.5 mm). Several sets of parameters were tested for the studied treatment plans. For the analysis, we choosed four parameters: the gamma score, the mean gamma, the number of detectors taken into account in the statistics and the median dose. A comparison with the results obtained by VARIAN's Portal Dose Image Prediction (PDIP) solution was also carried out to indicate the limits of these two pretreatment control methods. Results: Statistical and rational analyzes show that an optimal parameter set makes it possible to verify that the Delta 4PT can be used for all types of dynamic conformal arctherapy treatment plans. Initial results show that the absolute dose measured with The Delta 4PT is correct with an average median dose of −0.4% and a standard deviation of 0.75%. The gamma score (2%/2 mm) systematically passes the criteria of the 95% of points having a gamma of less than 1. Moreover, the results obtained for the PDIP are similar. Conclusions: A threshold of 30% with a 2%/2 mm criteria on the local gamma seems to be a good compromise for all field sizes. The physical and dosimetric characteristics of the Delta 4PT phantom allow it to be integrated into a quality assurance plan, whether in classic VMAT or stereotactic radiotherapy.